2019
DOI: 10.20853/33-3-3199
|View full text |Cite
|
Sign up to set email alerts
|

The profile of occupational stress in a sample of health profession academics at a historically disadvantaged university in South Africa

Abstract: Background: Higher education is a high stress occupation or environment. Academics in health professions are engaged in professional training that adds clinical or profession-specific competencies to general academic and research outcomes. Academics in health professions assume many roles and must remain current in the practise of their professions that increases stress. Studies on occupational stress amongst health professions academics are lacking in the South African context. Objectives: To assess occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Studies reviewed reveal that intense job demands tend to trigger high levels of stress (Boyd et al, 2011;Darabi et al, 2017b;Simons et al, 2019) and burnout (Zábrodská et al, 2018). However, in an interesting study, Bell et al (2012) found that usual job demands and pressure made no difference to well-being.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies reviewed reveal that intense job demands tend to trigger high levels of stress (Boyd et al, 2011;Darabi et al, 2017b;Simons et al, 2019) and burnout (Zábrodská et al, 2018). However, in an interesting study, Bell et al (2012) found that usual job demands and pressure made no difference to well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the knowledge and understanding that we have in this field so far, there seems to be an agreement that academic staff experience high levels of stress and burnout and low levels of well‐being. Studies reviewed reveal that intense job demands tend to trigger high levels of stress (Boyd et al, 2011; Darabi et al, 2017b; Simons et al, 2019) and burnout (Zábrodská et al, 2018). However, in an interesting study, Bell et al (2012) found that usual job demands and pressure made no difference to well‐being.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations